2012
DOI: 10.5812/thrita.4264
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Angiotensin-Convertings Enzyme Inhibitory Effects of Medicinal Plants Used in Traditional Persian Medicine for Treatment of Hypertension: Screening Study

Abstract: Article type: Original Article Background: Angiotensin converting enzyme (ACE) inhibitors are used widely in the treatment of hypertension and heart failure. These inhibitors such as captopril and enalapril are derived from natural products. Materials and Methods: In the present study 135 plants used in Traditional Persian Medicine have been investigated for their angiotensin converting enzyme (ACE) inhibitory activity. They were selected on the basis of their usage as antihypertensive, cardiotonics & diuretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
0
27
1
Order By: Relevance
“…In the present study, the levels of serum ALT and AST, as biomarkers of hepatic function, were significantly increased in the group treated with APAP-alone. ALT and AST are simple and widely accepted biomarkers for hepatic dysfunction, indicating that the APAP-induced liver damage model was successfully developed in mice [14]. In the Alhagi sparsifolia treatment group, the serum level of AST and ALT were markedly attenuate has compared to the APAP treatment group, suggesting that Alhagi sparsifolia has potential for use as APAP intervention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, the levels of serum ALT and AST, as biomarkers of hepatic function, were significantly increased in the group treated with APAP-alone. ALT and AST are simple and widely accepted biomarkers for hepatic dysfunction, indicating that the APAP-induced liver damage model was successfully developed in mice [14]. In the Alhagi sparsifolia treatment group, the serum level of AST and ALT were markedly attenuate has compared to the APAP treatment group, suggesting that Alhagi sparsifolia has potential for use as APAP intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Uyghur ethno medicine describes, Alhagi sparsifolia as an antipyretic and anti-diarrhea that can be used without worries of toxicity [11]. Previous research has demonstrated that Alhagi sparsifolia possesses various pharmaceutical properties that provide benefits as an anti-inflammatory, antiviral, antibacterial, antihypertensive, hepatoprotective, and immunomodulatory agent [12][13][14]. To date, however, this herbal plant has only minimally been studied for its role as a hepatoprotective mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro ACE inhibitory activity was also investigated for P. harmala. It was observed that treatment resulted in 72% inhibition of ACE activity in the case of aqueous extract and 84% inhibition in the case of alcoholic extract (Kouchmeshky et al, 2012). The aqueous extract of seeds of P. harmala have also been demonstrated to have antispasmodic, anticholinergic, antihistaminic and antiadrenergic effects (Aqel and Hadidi, 1991).…”
Section: Traditional Medicinal Plants With Reported Mode Of Action Wmentioning
confidence: 94%
“…25 , terpenoids 26,27 , flavonoids, proanthocyanidins 28 , xanthones 29 , and peptides/amino acids 28,30 have been investigated for their ability to inhibit ACE, which could serve as model substances in the development of new ACE inhibitors. Recent study highlights 135 plants screened for their ACE inhibiting activity in which 52 species gave more than 50% ACE inhibition 31 .…”
Section: Phytoconstituents and Disorder Typementioning
confidence: 99%